Employee mindset and innovativeness: the moderating effects of social relationships and self-leadership among employees at selected government linked - companies (GLCs) / Mohd Safwan Ramli - Ramli, Mohd Safwan (2022)
Employee innovativeness increases organizations' chances to react to changes and discover new opportunities. It can also help foster competitive advantage as it allows organizations to build better products and services for their client. Innovativeness is also recognized as one of the important criteria in employment whereby, employers tend to look at the job candidates’ abilities in expressing themselves through their creative thinking skills. Innovative employee can lead to new ideas as people are introduced to diverse perspectives and pushed to think more deeply. Another benefit of collaboration is that people with different skills and knowledge can figure out creative ways to combine their assets to solve problems. The main purpose of this research was to investigate the moderating self-leadership and perceived organizational support towards the relationship between an employee mindset and employee innovativeness among Government Linked-Companies (GLCs). The five GLCs involved in this study were Khazanah, Proton, Axiata Berhad, MAS and EPF. A correlational study design was applied in this study and data were collected by using quota sampling. Data were obtained through a set of questionnaires comprised of four sections. A pilot study was done prior to the actual data collection process, validating the instruments used. Exploratory Factor Analysis was conducted to establish the components under investigation. Besides, the researcher used descriptive, correlational, multiple regression and hierarchical regression analysis to analyze the data obtained. The findings of this study revealed that there was a relationship between an employee mindset and employee innovativeness among employees at selected GLCs in Malaysia. Specifically, every dimension of employee mindset explained the variance of employee innovativeness. Adaptability was discovered to be the most influential dimension of employee mindset towards employee innovativeness, followed by the dimension of employee mindset. Through correlational analysis, it was also found that the cosmopolitanism dimension of employee innovativeness had the strongest relationship with employee mindset. In addition, hierarchical regression analysis discovered that social relationships and self-ledership moderate the relationship between an employee mindset and employee innovativeness. In fact, four dimensions from the social relationship and self-leadership were found to be significantly moderating the relationship between the two variables of employee mindset and employee innovativeness. The researcher proposed a few suggestions on how to improve adaptability, super leader, cognitive complexity, work culture and creative thinking among employees. For instance, employees were recommended to be active listeners to improve their adaptability, embrace social composure to improve their creative thinking, work culture and their leadership skills, in order to increase their levels of innovativeness. Additionally, the researcher also suggested that future research should be conducted in a larger population and on other GLCs in other settings with better sampling methodologies.